Antimicrobial and DNA-binding activity of alkaloids from glycosmis pentaphylla (retz.) dc. - Nurhaya binti Md Taib (Kulliyyah of Pharmarcy, International Islamic Unniversity Malaysia, 2014)
Glycosmis pentaphylla (Retz.) DC. has been traditionally used to cure various illnesses and conditions such as fever, eczema and rheumatism. The present study was designed to evaluate the antimicrobial and DNA binding activities of the alkaloids isolated from the plant. Leaves and stem bark of G. pentaphylla were extracted by continuous extraction using hexane and acetone prior to acid base extraction. Screening of alkaloids available was done by Thin Layer Chromatography (TLC). Fractionation by column chromatography was employed to separate the extract into fractions of alkaloid compounds. Antimicrobial active alkaloids were screened by TLC Agar Overlay Assay against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Candida albicans ATCC 90028. The alkaloids were isolated by using column chromatography and were authenticated by comparing their TLC profile, maximum wavelength for UV absorption in methanol and melting point to that of authentic alkaloids. The identification of the alkaloids was further confirmed by their NMR spectral data. The antimicrobial activity of the alkaloids was determined quantitatively by means of their Minimum Inhibitory Concentration (MIC) and Minimum Microbiocidal Concentration (MMC) by using broth microdilution assay. Antimicrobial combination effects between the active alkaloids and selected antimicrobial agents, which were erythromycin and vancomycin was studied by cherkerboard assay and determined by their Fractional Inhibitory Concentration Index (FICI). DNA binding activity of the alkaloids was investigated by method using restriction enzymes and specially designed 1.5 kb DNA fragment. Three antimicrobial active alkaloids labeled as GP3-3, GP6-2 and GP11-2 were detected, isolated, authenticated and identified as arborinine, arborine and skimmianine respectively. Antimicrobial activity of arborinine and arborine were ranged between 250 µg/mL and 1000 µg/mL. Arborinine and arborine showed lowest MIC values of 250 µg/mL and 500 µg/mL respectively which were against C. albicans. Arborine displayed high MIC values against all other microbes while arborinine was weak against S. aureus, E. coli and P. aeruginosa. No synergistic effect was observed from the combination of the alkaloids with the selected antimicrobial agents against Gram positive, S. aureus, Gram negative E. coli and fungi, C. albicans. However, partial synergy was reported for all interactions between arborine and antimicrobial agents against S. aureus and interaction between arborinine and ketoconazole against C. albicans. Additive effect was only produced when arborine was combined with vancomycin while antagonism was observed for the interaction between arborine and ciprofloxacin when tested against E. coli. All alkaloids displayed photo activated DNA binding activity by strength in the order of arborine, arborinine and skimmianine.